Customers' awareness towards products offered by Budayatama Corporation Sdn Bhd / Rafidah Isa - Isa, Rafidah (Faculty of Business and Management, 2007)
The study is based on the customer awareness towards the product offerings by Budayatama Corporation Sdn Bhd. Products can be classified as either business (industrial) or consumer products, depending on the buyer's intentions. The key distinction between the two types of products is their intended use. If the intended use is a business purpose, the product is classified as a business or industrial product. A business product is used to manufacture other goods or services, to facilitate an organization's operations, or to resell to other customers. A consumer product is bought to satisfy an individual's personal wants